2021
DOI: 10.1242/dev.199166
|View full text |Cite
|
Sign up to set email alerts
|

Direct repression of Nanog and Oct4 by OTX2 modulates the contribution of epiblast-derived cells to germline and somatic lineage

Abstract: In mammals, the pre-gastrula proximal epiblast gives rise to primordial germ cells (PGCs) or somatic precursors in response to BMP4 and WNT signaling. Entry into the germline requires activation of a naïve-like pluripotency gene regulatory network (GRN). Recent work has shown that suppression of OTX2 expression in the epiblast by BMP4 allows cells to develop a PGC fate in a precise temporal window. However, the mechanisms by which OTX2 suppresses PGC fate are unknown. Here, we show that, in mice, OTX2 prevents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 59 publications
(76 reference statements)
0
11
0
Order By: Relevance
“…In the absence of cytokines, OTX2 protein levels are sufficient to block activation of the PGCLC programme. Recent findings indicate that this repressive effect of OTX2 on the PCG programme results in large part from a direct repression of the Nanog and Oct4 genes (Figure 4A) (Di Giovannantonio et al, 2021). Induction of transgenic Nanog in EpiLCs shifts the balance between the mutual antagonists NANOG and OTX2 in favour of NANOG (Figure 4B).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In the absence of cytokines, OTX2 protein levels are sufficient to block activation of the PGCLC programme. Recent findings indicate that this repressive effect of OTX2 on the PCG programme results in large part from a direct repression of the Nanog and Oct4 genes (Figure 4A) (Di Giovannantonio et al, 2021). Induction of transgenic Nanog in EpiLCs shifts the balance between the mutual antagonists NANOG and OTX2 in favour of NANOG (Figure 4B).…”
Section: Discussionmentioning
confidence: 96%
“…In contrast, Otx2 deletion dramatically increases PGCLC numbers in vitro and raises PGC numbers in vivo (J. . Recently, OTX2 has been shown to act through cis-acting binding sites that repress transcription of Nanog and Oct4 (Di Giovannantonio et al, 2021). However, despite an increasing knowledge of the relationships between Esrrb, Nanog and Otx2, the interplay between these factors in PGC induction is not completely understood.…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of cytokines, OTX2 protein levels are sufficient to block activation of the PGCLC program. Recent findings indicate that this effect of OTX2 on the PCG program results largely from direct repression of Nanog and Oct4 ( Figure 4 A) ( Di Giovannantonio et al., 2021 ). Induction of transgenic Nanog in EpiLCs shifts the balance between the mutual antagonists NANOG and OTX2 in favor of NANOG ( Figure 4 B).…”
Section: Discussionmentioning
confidence: 97%
“…We have shown that entry to the germline is blocked when OTX2 expression is maintained during the first 2 days of EpiLC-PGCLC differentiation (Zhang et al, 2018a;Zhang and Chambers, 2019). In contrast, Otx2 deletion dramatically increases PGCLC numbers in vitro and raises PGC numbers in vivo (Zhang et al, 2018a) (legend continued on next page) Giovannantonio et al, 2021). However, despite increasing knowledge of the relationships among ESRRB, NANOG, and OTX2, the interplay among these factors in PGC induction is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation